Choosing event‐driven and daily HIV pre‐exposure prophylaxis – data from two European PrEP demonstration projects among men who have sex with men. Issue 8 (12th August 2021) - Jongen, Vita W; Reyniers, Thijs; Ypma, Zorah MH; Schim van der Loeff, Maarten F; Davidovich, Udi; Zimmermann, Hanne ML; Coyer, Liza; van den Elshout, Mark AM; de Vries, Henry JC; Wouters, Kristien; Smekens, Tom; Vuylsteke, Bea; et al.
Abstract: Introduction: Daily and event‐driven PrEP are both efficacious in reducing the risk for HIV infection. However, the practice of event‐driven PrEP (edPrEP) is less well studied, in particular when provided as an alternative to daily PrEP. We studied regimen preferences and switches, and sexually transmitted infection (STI) incidence. Methods: We analysed pooled data from two prospective cohort studies among MSM: Be‐PrEP‐ared, Belgium and AMPrEP, the Netherlands. In both projects, participants could choose between daily and edPrEP at three‐monthly study visits, when they were also screened for sexually transmitted infections including hepatitis C (HCV). We assessed the proportion choosing each regimen, and the determinants of choosing edPrEP at baseline. Additionally, we compared the incidence rates (IRs) of HCV, syphilis and chlamydia or gonorrhoea between regimens using Poisson regression. The study period was from 3 August 2015 until 24 September 2018. Results and discussion: We included 571 MSM, of whom 148 (25.9%) chose edPrEP at baseline. 31.7% of participants switched regimen at least once. After 28 months, 23.5% used edPrEP. Older participants (adjusted odds ratio (aOR) = 1.38 per 10 years, 95% confidence interval (CI) = 1.15 to 1.64) and those unemployed (aOR = 1.68, 95% CI = 1.03 to 1.75) were more likely to initially choose edPrEP. IR of HCV and syphilis did not differ between regimens, but the IR of chlamydia/gonorrhoea was higher among daily users (adjusted incidence rate ratio = 1.61, 95% CI = 1.35 to 1.94). Conclusions: A quarter of participants chose edPrEP at baseline and at 28 months this proportion was similar. Although the IR of HCV and syphilis were similar in the two regimens, the lower incidence of chlamydia and gonorrhoea among edPrEP users may suggest that less frequent STI testing of this group could be considered.